2018
DOI: 10.1016/j.pedneo.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of SPARK on social and motor skills of children with autism

Abstract: The results of this study suggest that the SPARK's training can be considered as a therapeutic option not only for motor enhancement but also for improving social skills in children with ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(92 citation statements)
references
References 30 publications
6
76
0
10
Order By: Relevance
“…In general, swimming pools serve as a hub for all sorts of activities, social gatherings, and community activities. For instance, study results of Pan (2010) and Najafabadi et al (2018) argue that group aquatic activities create an adapted atmosphere in which a child or an adolescent with ASD interact with other people, even if he or she has never met before. From a social development standpoint, this aspect of group work in the water can be valuable as a child learns how to interact and be confident around different personalities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In general, swimming pools serve as a hub for all sorts of activities, social gatherings, and community activities. For instance, study results of Pan (2010) and Najafabadi et al (2018) argue that group aquatic activities create an adapted atmosphere in which a child or an adolescent with ASD interact with other people, even if he or she has never met before. From a social development standpoint, this aspect of group work in the water can be valuable as a child learns how to interact and be confident around different personalities.…”
Section: Discussionmentioning
confidence: 99%
“…Although in a few studies, such as the one of Fragala-Pinkham et al (2011) and Najafabadi et al (2018) there are provided descriptions in which parents assessed participants with structured scales and subscales. The findings showed that on the programme satisfaction questionnaire, parents reported high levels of satisfaction with the programme activities.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations